Analysis of SMEs Culinary Marketing Strategy During Covid 19 Pancemic: A Study at “Sate Bebek Cilegon” Resto in Cilegon, Banten - Marissa Grace Haque; Munawaroh Munawaroh; Denok Sunarsi (International Journal of Education, Information Technology, and Others, 2020)
The Covid 19 pandemic opens wider horizons of all of us, related to how to survive in the midst of business uncertainty and layoffs everywhere. Based on the theory of Basic Needs "A Theory of Human Motivation", from Abraham Maslow (1943), stated that food is one of the most important basic needs to take precedence, besides clothing and shelter. Amid PSBB (mild lockdown) until the time of easing, the digital business world is a temporary solution for the wider community throughout the world, especially in Cilegon, Banten, related to the dynamics of culinary commerce among citizens. Marketing that is preceded by strategies in planning steps is the most appropriate in the current pandemic situation, especially using digital media, which is inevitable. Because the world of IT-ICT now makes the world in our hands and become all of us without exception. For this reason, strategies and breakthroughs in order to survive and increase the competitiveness of the company to be able to survive and win in the competition are interesting to analyze the company's internal and external environment. In analyzing the SWOT analysis method used to weight the level of importance of each actor and factor. From the IE Matrix test, the competitive position of the Sate Bebek Cilegon restaurant is obtained in the quadrant or cell IV of IE Matrix, with a growth concentration strategy through horizontal integration. By looking at the position: (1) competing; (2) strength; (3) weaknesses; (4) opportunity; and (5) threats. In this case the Sate Bebek Cilegon restaurant must use a strategy: (1) market penetration; (2) market development; and also (3) horizontal integration strategies besides creating creative innovation must also be carried out.